Risk factors and primary prevention of upper gastrointestinal bleeding: an integrative review (Research, Society and Development, 2022)
Digestive hemorrhages are among the most frequent emergencies in Brazilian health services, requiring hospitalization in a high percentage of patients, with upper digestive hemorrhages being more prevalent than lower digestive hemorrhages. This is an integrative literature review, carried out from the analysis of scientific articles with evidence-based searches and the use of the acronym PICO strategy. The objective is to evaluate, through an integrative review, the main risk factors for the development of upper gastrointestinal bleeding and forms of primary bleeding prophylaxis. After crossing the descriptors in the databases and filtering based on the inclusion and exclusion criteria, 6 studies were selected to make up the final sample. The studies reaffirm what is already evidenced in the literature, reaffirming as the main risk factors for the development of ADH: peptic ulcer, esophageal varices, liver cirrhosis, use of drugs that damage the gastric mucosa such as nonsteroidal anti-inflammatory drugs, H infection Pylori, male gender, old age, kidney failure and unhealthy lifestyles. However, such risk factors are not in the public domain in terms of understanding what causes their development and what risks they bring to health. It is necessary on the part of health professionals greater dedication to health education, especially in the context of low complexity and primary care, promoting the dissemination of knowledge that provide a foundation for self-care.